2009
DOI: 10.1210/jc.2009-1231
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Outcome in Women with Type 2VersusType 1 Diabetes Mellitus: A Systematic Review and Metaanalysis

Abstract: Despite a milder glycemic disturbance, women with type 2 DM had no better perinatal outcomes than those with type 1, indicating that type 2 DM in pregnancy is a serious condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
200
7
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(224 citation statements)
references
References 44 publications
14
200
7
3
Order By: Relevance
“…Increased efforts are also needed to educate and empower women with type 2 diabetes, who have the lowest rates of attendance for preconception care (19 vs. 35% in women with type 1 diabetes) (26). Women with type 2 diabetes tend to be of lower socioeconomic status and include many ethnic minorities and new immigrants, making the challenges of preconception awareness and care more difficult (27).…”
Section: Discussionmentioning
confidence: 99%
“…Increased efforts are also needed to educate and empower women with type 2 diabetes, who have the lowest rates of attendance for preconception care (19 vs. 35% in women with type 1 diabetes) (26). Women with type 2 diabetes tend to be of lower socioeconomic status and include many ethnic minorities and new immigrants, making the challenges of preconception awareness and care more difficult (27).…”
Section: Discussionmentioning
confidence: 99%
“…Pregestational BMI and gestational weight gain in nulliparous women with type 1 DM has been reported to be associated with an increased rate of cesarean section [22]; therefore, diet therapy may play an important role in the management of pregnant women with DM. A meta-analysis by Basells et al showed that HbA1c levels at booking were higher in type 1 DM patients, with similar congenital malformation rates in women with type 1 and type 2 DM, and lower rates of diabetic ketoacidosis and cesarean section in type 2 DM patients than in type 1 DM patients [23]. This metaanalysis summarized pregnancy outcomes in women with type 1 and type 2 DM worldwide over 20 years; however, the progress and improvement in the management for diabetes was not evaluated by this study.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, regular effective follow-up reduces the risk of undiagnosed type 2 diabetes predating a subsequent pregnancy, and the increased risk to mother and foetus associated with such an event (3).…”
Section: Introductionmentioning
confidence: 99%